Humanizing education: reflecting the Sejahtera Academic Framework based on the psychosocial needs of students - Abdul Wahid, Nur Kamariah (Kulliyyah of Economics and Management Sciences International Islamic University Malaysia, 2021)
This paper is intending as an illustration paper in reflecting the Humanizing Education with Maqasid al-Shari‟ah Dimensions‟ session on day 3 of the KENMS „Ibadah Camp. The author is trying to put the ideas behind the framework into more doable practices, not just as a rhetoric idea to stay on a nicely designed framework. The essay is constructed to reflect the understating on how to relate and make the framework becoming operationalise into daily activities as a learning facilitator at the Department of Business, engaging with the students on seeing the knowledge shared into more understandable manner, hence reflected into the quality of them as graduate of IIUM spreading the right understanding of the knowledge within the right understanding of Islam comprising of strong adherence to Quran and Sunnah.